CHARACTERISTIC AND HISTOPATHOLOGICAL FEATURES OF PATIENTS WITH PERFORATED PEPTIC ULCER WHO UNDERWENT OPEN SURGERY THERAPY AT DR.SOETOMO GENERAL ACADEMIC HOSPITAL, SURABAYA, INDONESIA - Alfi Nureta Rachmani; Mamiek Dwi Putro; Alphania Rahniayu (Majalah Biomorfologi, 2021)
Background: Perforated peptic ulcer is a form of complications from peptic ulcer and one of the most common emergency conditions in medicine. Objective: To describe the characteristic and histopathological features of patients with perforated peptic ulcer who underwent open surgery therapy in Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. Materials and Methods: This study was a descriptive study by observing patients’ data from medical records (secondary data) at Medical Record Center of Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, in 2016. Data obtained were analyzed descriptively. Results: Forty-six patients were identified (34 male, 12 female), most of them were between 56-65 years old for male and ≥66 years old for female. Majority of the subjects had a history of herbal medicine consumption (54%) as risk factors for developing perforated peptic ulcer and the most frequent comorbid diseases were diabetes and hypertension. The histopathological features found mostly were inflammation (100%), necrosis (44%), fibrosis (36%), granulation (17%) and  positive Helicobacter pylori (6%). Conclusion: Majority of the subjects were male, mostly between 56-65 years old for male and ≥66 years old for female. The histopathological features showed that all subjects had inflammations.